Transformative Impacts of Chinese FDI: Catalyzing Technological Advancements and Economic Growth in Morocco - Touati, Younes; Jingjie, Feng; Ahmed, Mohamed Salah Adawi (International Journal of Scientific Research and Management (IJSRM), 2024)
Foreign Direct Investment (FDI) plays a vital role in shaping the global economic landscape, driving growth, spurring technological innovation, and enhancing international competitiveness. This paper embarks on a deep dive into the multifaceted world of FDI, unraveling its core concepts, theoretical underpinnings, influencing factors, and profound economic impacts. Focusing on Morocco, the study traces the evolution and current status of FDI, showcasing the nation's strategic initiatives since the reform and opening up era aimed at magnetizing foreign investments. Through illuminating case studies of Chinese FDI in Morocco, the paper reveals the transformative effects on economic development, job creation, and technological transfer. The findings highlight the crucial need for optimizing the investment climate, boosting innovation capabilities, and fostering regional development to attract premium foreign investments and ensure long-term economic vitality.